Cambio en la mortalidad intrahospitalaria durante el primer pico por SARS- COV-2 en Bogotá, Colombia - Stephany Barbosa (Asociación Colombiana de Infectología, 2021)
Introduction: Mortality secondary to SARS-COV 2 has decreases around the world, however this has not been evaluated in Colombia neither has the correlation between patient characteristics or treatments.Objective: To compare the mortality due to SARS-COV-2, in two periods of time, controlling risk factors associated with mortality.Methodology: Observational retrospective cohort study of patients with SARS- COV-2 treated at the San Ignacio University Hospital in Bogotá (Colombia), from March 19 to November 12, 2020. The in-hospital mortality rate of patients discharged before and after August 21, 2020 (surge mortality in Colombia) was com-pared. The impact of the moment of attention was analyzed controlled by comorbidities, severity at admission and treatment received using a bivariate and multivariate logistic regression model.Results: 1399 patients (944 before and 455 after August 21) were analyzed. The overall in-hospital mortality rate was similar at both times (17.6%vs16.3percentage, p=0.539). In the multivariate analysis, it was found that the moment of attention was associated with lower mortality (OR 0.66 95% CI0.47;0.93,p=0.018), in contrast to its increase associated with age (OR 1.06 95% CI 1.05;1.07,p=<0.001), male sex (OR 1.84 95%CI 1.33;2.54,p=<0.001), cirrhosis (OR1.89 95%CI 1.24;2.88, p=0.003), kidney disease (OR 1.36 95% CI1.00;1.83,p=0.043) and the use of dexamethasone (OR1.53 95%CI 1.03;2.28,p=0.031).Conclusions: The in-hospital mortality rate fell after August 21 during the first wave of the pandemic in Bogotá-Colombia, possibly associated with an improvement in response capacity, or a lower viral inoculum of infected patients. These findings may change with the saturation of the health system.